Strength of Materials - Jaramillo, Héctor S.; Arnaldo Avila, Julian; Chen, Can (IntechOpen, 2020)
In materials, their strength is the ability to bear an applied load before their failure. In this direction, the Strength of Materials studies the stresses and deformations that happen in materials as an outcome of loads acting on them. The book contains eleven peer-reviewed chapters organized into two sections. Section 1 is focused on the strength of metals and composites materials, in other words on traditional materials used in engineering projects. Section 2 contains chapters on sustainable materials or non-conventional materials. We sincerely hope that you enjoy this book and the contents will help in the dissemination of knowledge to researchers and students working with materials and their applications.